Targeted drug delivery to circulating tumor cells via platelet membrane-functionalized particles. (January 2016) - Li, Jiahe; Ai, Yiwei; Wang, Lihua; Bu, Pengcheng; Sharkey, Charles C.; Wu, Qianhui; Wun, Brittany; Roy, Sweta; Shen, Xiling; King, Michael R.
Abstract: Circulating tumor cells (CTCs) are responsible for metastases in distant organs via hematogenous dissemination. Fundamental studies in the past decade have suggested that neutralization of CTCs in circulation could represent an effective strategy to prevent metastasis. Current paradigms of targeted drug delivery into a solid tumor largely fall into two main categories: unique cancer markers (e.g. overexpression of surface receptors) and tumor-specific microenvironment (e.g. low pH, hypoxia, etc.). While relying on a surface receptor to target CTCs can be greatly challenged by cancer heterogeneity, targeting of tumor microenvironments has the advantage of recognizing a broader spectrum of cancer cells regardless of genetic differences or tumor types. The blood circulation, however, where CTCs transit through, lacks the same tumor microenvironment as that found in a solid tumor. In this study, a unique "microenvironment" was confirmed upon introduction of cancer cells of different types into circulation where activated platelets and fibrin were physically associated with blood-borne cancer cells. Inspired by this observation, synthetic silica particles were functionalized with activated platelet membrane along with surface conjugation of tumor-specific apoptosis-inducing ligand cytokine, TRAIL. Biomimetic synthetic particles incorporated into CTC-associated micro-thrombi in lung vasculature and dramatically decreased lung metastases in a mouse breast cancer metastasis model. Our results demonstrate a "Trojan Horse" strategy of neutralizing CTCs to attenuate metastasis.